Studi Kajian Sektor Moneter terhadap Stabilitas Sistem Keuangan di Indonesia - Sisiliana Sisiliana; Devani Pratiwi; Vanny Euorita Tarigan; Samuel Frans Deo; Zuziva Apriliani Dewi; Dewi Mahrani Rangkuty (Student Research Journal, 2023)
The financial system plays a critical role in the economy. If the financial system is unstable and does not function efficiently, the allocation of funds will not go well, which can hamper economic growth. This study aims to analyze the influence of the monetary sector on financial system stability in Indonesia. This qualitative descriptive study with literature method through literature study using secondary data obtained from the Indonesian Central Bureau of Statistics. The study's results explain that the exchange rate or exchange rate and inflation can affect the stability of the financial system in Indonesia.